1989
DOI: 10.1073/pnas.86.10.3479
|View full text |Cite
|
Sign up to set email alerts
|

Plasmenylethanolamine is the major storage depot for arachidonic acid in rabbit vascular smooth muscle and is rapidly hydrolyzed after angiotensin II stimulation.

Abstract: The present study demonstrates that rabbit aortic intimal smooth muscle cells contain the majority of their endogenous arachidonic acid mass in plasmenylethanolamine molecular species. To demonstrate the potential significance of these plasmenylethanolamines as substrates for the smooth muscle cell phospholipases that are activated during agonist stimulation, aortic rings were prelabeled with [3H]arachidonic acid and stimulated with angiotensin II. Although the specific activities of the choline and inositol g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 23 publications
(12 reference statements)
2
71
0
Order By: Relevance
“…Plasmalogens are a predominant phospholipid molecular subclass found in many mammalian tissues including endothelial cells and vascular smooth muscle (16,35). Vascular tissue is one of the major pathophysiological host targets of activated leukocytes leading to inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmalogens are a predominant phospholipid molecular subclass found in many mammalian tissues including endothelial cells and vascular smooth muscle (16,35). Vascular tissue is one of the major pathophysiological host targets of activated leukocytes leading to inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmalogens are a subclass of glycerophospholipids found both in the plasma membrane phospholipid pools of many mammalian tissues and in lung surfactant (12)(13)(14)(15)(16)(17)(18). Plasmalogens possess a masked aldehyde, vinyl ether linkage between the sn-1 aliphatic chain and the glycerol backbone and may have an important role in both the solvation of transmembrane ion channels and transport proteins as well as the storage of arachidonic acid (19 -22).…”
mentioning
confidence: 99%
“…They are responsible for most of the known physiological actions of All, via interactions with a Gprotein which activates phospholipase C (PLC) (Morrero et al, 1994). All also stimulates phospholipase A2 (PLA2), leading to the release of arachidonate and its metabolic products (Ford & Gross, 1989). Genome analyses and homology cloning demonstrated that there are two subtypes of AT, receptors, ATlA and ATIB, which are encoded by two different genes in the rat (Lewis et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…11 Plasmalogens are a predominant membrane constituent in many cells of the cardiovascular system, and they contain a sn-1 vinyl ether bond. [12][13][14] In vitro plasmalogen oxidation by MPO-derived reactive chlorinating species (RCS) results in the release of the ␣-chloro fatty aldehyde species, 2-chlorohexadecanal (2-ClHDA) and 2-chlorooctadecanal (2-ClODA), from the sn-1 position with concomitant production of sn-1 lysophospholipids through a phospholipaseindependent mechanism. 15,16 Demonstration that MPOcatalyzed oxidation of plasmalogens in vivo with concomitant production of novel ␣-chloro fatty aldehydes and sn-1 lysophosphatidylcholine (LPC) has not yet been reported.…”
mentioning
confidence: 99%